Slowly Wrecking Our Planet - Bertell, Rosalie (Canadian Woman Studies/les cahiers de la femme, 2016)
Cet article est le dernier que Rosalie Bertell a publié en 2011 avant sa mort en 2012. Elle a colligé les résultats importants de sa recherche sur le développement d’un mouvement secret de géo-militarisme qui a partiellement détruit la vie sur notre planète depuis déjà des décennies. Le dérèglement de la température, les changements climatiques, les catastrophes naturelles toujours plus violentes et fréquentes résulteraient de ces manipulations dans le monde. Au lieu d’enquêter sur cette situation, la récente science de la géo-ingénierie tente de sauver la planète épuisée mais paradoxalement elle propage les mêmes mesures qui ont causé les problèmes. Un débat public s’impose autour de ces nouvelles technologies, mais il n’est pas encore développé. This is the last article Rosalie Bertell wrote in 2011 before she passed in 2012. In this article, her aim is to gather the most important results of her research about the development of a secret “geo-warfare” that is threatening, and has already partly destroyed, the life systems of our planet. Increasing freak weather conditions, climate changes, and seemingly “natural” catastrophes around the world are the possible result of these undertakings by the military worldwide. Further, a recently appearing civil science of “geo-engineering” today presents itslef as the “saviour” of a planet under stress, paradoxically propagating the same measures that may be at the root of the current climate crisis. A public debate of the background and development of these new technologies has not yet taken place.